Monitoring the Stability of Oxygen Flow Analyzer on Oxygen Station in the Hospital - Nur Khabibatul Rosida; Triana Rahmawati; Maduka Nosike; I Dewa Gede Hari Wisana (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Oxygen therapy besides having benefits also has certain dangers and side effects. For this reason, oxygen therapy must be given at the proper dose by monitoring the patient regularly and adjusting the oxygen flowmeter. The accuracy of flowmeter under standard conditions is guaranteed by manufacturer. With time and use the precision may change and the flow accuracy given in a hospital setting may differ from the original value. Thepurpose of this research is to conduct further research on Oxygen flow analyzer which focuses on discussing the accuracy and stability of the oxygen flow sensor against the gold standard. Contribution of this study is to increase the range of oxygen flowrate measurement to 15 liters per minute (LPM). This research uses Arduino Mega while the gas flow sensor used is legris flow sensor. The measurement results are displayed on TFT LCD equipped with SD Card data storage. The gas flowrate is regulated using a flowmeter (GEA). Meanwhile the comparison tools using Oxygen Analyzer and 1 m3 oxygen gas cylinder. At the testing stage, the sensor reading value on the module that appears on the TFT LCD is compared with the resultsf a comparison tool with a measurement range of 1 LPM to 15 LPM 6 times at each point. The conclusion from these results is that the calibrator module has a relative error is still within the allowable tolerance limit of ±10%. INDEX TERMS Calibration, Oxygen Flow Analyzer, Flowmeter, TFT Display